Seasonal Molecular Difference in Fibrillar Collagen Extracts Derived from the Marine Sponge Chondrosia reniformis (Nardo, 1847) and Their Impact on Its Derived Biomaterials - Tassara, E.; Orel, B.; Ilan, M.; Cavallo, D.; Dodero, A.; Castellano, M.; Vicini, S.; Giovine, M.; Pozzolini, M. (Marine Drugs, 2023)
Chondrosia reniformis (Nardo, 1847) is a marine sponge of high biotechnological interest both for its natural compound content and for its peculiar collagen, which is suitable for the production of innovative biomaterials in the form, for instance, of 2D membranes and hydrogels, exploitable in the fields of tissue engineering and regenerative medicine. In this study, the molecular and chemical?physical properties of fibrillar collagen extracted from specimens collected in different seasons are studied to evaluate the possible impact of sea temperature on them. Collagen fibrils were extracted from sponges harvested by the Sdot Yam coast (Israel) during winter (sea temperature: 17 ?C) and during summer (sea temperature: 27 ?C). The total AA composition of the two different collagens was evaluated, together with their thermal stability and glycosylation level. The results showed a lower lysyl-hydroxylation level, lower thermal stability, and lower protein glycosylation level in fibrils extracted from 17 ?C animals compared to those from 27 ?C animals, while no differences were noticed in the GAGs content. Membranes obtained with fibrils deriving from 17 ?C samples showed a higher stiffness if compared to the 27 ?C ones. The lower mechanical properties shown by 27 ?C fibrils are suggestive of some unknown molecular changes in collagen fibrils, perhaps related to the creeping behavior of C. reniformis during summer. Overall, the differences in collagen properties gain relevance as they can guide the intended use of the biomaterial.